2010
DOI: 10.1111/j.1365-294x.2010.04647.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by environmental distance in mobile marine species: molecular ecology of franciscana dolphins at their southern range

Abstract: The assessment of population structure is a valuable tool for studying the ecology of endangered species and drafting conservation strategies. As we enhance our understanding about the structuring of natural populations, it becomes important that we also understand the processes behind these patterns. However, there are few rigorous assessments of the influence of environmental factors on genetic patterns in mobile marine species. Given their dispersal capabilities and localized habitat preferences, coastal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
149
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 121 publications
(160 citation statements)
references
References 61 publications
8
149
2
1
Order By: Relevance
“…(2010) reported that their BASW location, near RN, did not differ from their BAS location (named as NC and CL in this study). Based on the published information of that study, we were not able to compare our results with neither BASW nor BAS.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…(2010) reported that their BASW location, near RN, did not differ from their BAS location (named as NC and CL in this study). Based on the published information of that study, we were not able to compare our results with neither BASW nor BAS.…”
Section: Discussionmentioning
confidence: 67%
“…Overall, similar levels of genetic variation for both the microsatellite and mtDNA data were observed between localities in this study (Tables 1 and 4), and these were comparable with those previously found in the FMA IV (Méndez et al., 2008; Méndez, Rosenbaum, Subramaniam, et al., 2010). We found that MH and RN presented several private alleles, in comparison with NC and CL (Table 1), and that these were found in all, but one case, at the edges of the allele sizes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations